PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBASIS NILAI TANGGUNG JAWAB MENJAGA LINGKUNGAN PADA SISWA FASE A SEKOLAH DASAR - Yudha Aldetya Fanda Febriarta; Muhammad Ainur Rasikin; Fahriz Anam Wijaya; Mujtahidin (STKIP Subang, 2026)
The low level of students’ environmental awareness and limited availability of engaging learning media serve as the background of this research. This study aims to develop digital comic learning media based on environmental responsibility values that are valid and effective for use in Phase A elementary school learning. The research employs the Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Research subjects were 9 second-grade students of SDN Banyuajuh 4. Material expert validation obtained a score of 86% in the very feasible category, and media expert validation obtained 89% in the very feasible category. The effectiveness test through N-Gain calculation showed a score of 0.7 in the moderate-high category, with a pretest average of 65 and posttest average of 88. Therefore, the developed digital comic media is declared valid and effective as learning media for environmental responsibility values among Phase A elementary school students.